IMPLEMENTASI METODE PEMBELAJARAN DISCOVERY LEARNING BERBANTU MOODLE PADA MATAKULIAH EKONOMI REGIONAL - Fitri Astuti, Rika Pristian; Jazilatul Kholidah, Neneng Rika; Tirtanawati, Meiga Ratih (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
The problem of this research is that lecturers' learning is less precise in using learning methods so that students are less active and learning outcomes or student scores are low. This study aims to determine the implementation of learning using the Moodle-assisted discovery learning method, knowing the strengths and weaknesses of Moodle learning. The research design uses descriptive with a qualitative approach. Sources of data were obtained from students majoring in economics education in 6th semester. Data collection techniques using observation and interviews. Data analysis techniques use data collection, data reduction, data display, and drawing conclusions. The results of this study learning using the Moodle-assisted discovery learning method can help e-learning learning for students and is very effective to apply to the learning process. In learning using Moodle, the lecturer provides explanations to students through PowerPoint and YouTube which are uploaded with the aim that students can understand the material at any time and students can discuss with their friends. The advantages of doing Moodle learning are that learning is easier, more relaxed, the material provided by lecturers is more concise and students find it easier to access subject matter, working on assignments takes quite a long time. The disadvantages of Moodle are that the learning process is less effective, there are students who have difficulty understanding the material because they do not get direct explanations from the lecturer, and the internet network is less supportive.